Peningkatan Kapasitas Ibu Hamil Melalui Buku KIA Kelas Ibu Hamil Tahun 2024 - Yuniarti; Zakiah; Hapisah; Fitria Jannatul Laili; Efi Kristiana; Suryanti; Riska; Runa Helmina; Rusmia Azizah (Health Care : Journal of Community Service, 2024)
Health development programs in Indonesia are currently prioritized towards improving the health status of mothers and children, particularly in the most vulnerable groups such as pregnant women, mothers giving birth, perinatal infants, toddlers, and women of reproductive age. In response to this, a community service activity titled "Enhancing the Capacity of Pregnant Women through the Maternal and Child Health (MCH) Handbook in Pregnant Women's Classes in the Working Area of Puskesmas Cempaka, Banjarbaru City, in 2024" was conducted. This initiative aims to reduce child mortality rates and improve maternal health. The use of the MCH Handbook is considered a strategic step to enhance community independence. The target of this community service activity was 12 pregnant women attending the Pregnant Women's Class facilitated by Midwife Maulida. The implementation methods included preparation and execution of activities in June 2024 in Bangkal, Cempaka Subdistrict, Banjarbaru City. Evaluations were conducted through pre-test and post-test assessments of the mothers' knowledge about the MCH Handbook. The results showed that 83% of the participants always brought the MCH Handbook during antenatal visits, 41.6% had read the handbook in its entirety, and 58.3% only read the sections related to examinations. Therefore, further evaluations of pregnant women's knowledge about pregnancy through the MCH Handbook are needed to broaden their insights and enable effective implementation.